2012
DOI: 10.1002/qj.1919
|View full text |Cite
|
Sign up to set email alerts
|

Super‐Clausius–Clapeyron scaling of rainfall in a model squall line

Abstract: The sensitivity of squall rainfall to changes in atmospheric temperature is investigated. For instantaneous rainrates and accumulations up to one hour, extreme rainfall scales with Clausius-Clapeyron (CC) for temperatures below 24• C and at up to twice CC above 24• C. For longer accumulation periods and higher temperatures the scaling breaks down due to increased propagation of the squall line. For all periods, the storm average rainfall is found to scale at approximately 1.5 times CC over the entire range of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
78
6

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(88 citation statements)
references
References 15 publications
4
78
6
Order By: Relevance
“…The CC or below CC rates are mainly followed by long, synoptic, colder rain, while the super CC is mainly found in short-lived, warmer convective rain (Panthou et al, 2014;Lenderink et al, 2011;Mishra et al, 2012;Singleton and Toumi, 2013).…”
Section: The P I -T D Relationmentioning
confidence: 99%
“…The CC or below CC rates are mainly followed by long, synoptic, colder rain, while the super CC is mainly found in short-lived, warmer convective rain (Panthou et al, 2014;Lenderink et al, 2011;Mishra et al, 2012;Singleton and Toumi, 2013).…”
Section: The P I -T D Relationmentioning
confidence: 99%
“…Observations [Lenderink and van Meijgaard, 2008] and recent simulations [Singleton and Toumi, 2012] have suggested that convective precipitation intensity may react in a substantially different way to temperature changes than is the case for stratiform precipitation. This hypothesis was recently backed by observational support for a midlatitude region by Berg et al [2013].…”
Section: Introductionmentioning
confidence: 99%
“…In the French Mediterranean region, Drobinski et al (2016) showed that the scaling of precipitation extreme displays a hook-like shape with a nearly CC-scaling at low temperatures and a negative slope at high temperatures, which they attribute to the arid environment in summer. Deviations from the CC scaling have been observed or simulated for several reasons such as precipitation accumulation duration (Utsumi et al 2011;Drobinski et al 2016), use of surface air temperature as a proxy of the tropospheric temperature (Hardwick Jones et al 2010;Drobinski et al 2016), change in precipitation type Berg and Haerter 2013), changes in the atmospheric dynamics (O'Gorman and Schneider 2009;Sugiyama et al 2010;Singleton and Toumi 2013;Muller 2013) which may be related to seasonal variability Drobinski et al 2016). Hence, the applicability of the CC scaling on the temperature-precipitation extremes relationship is still uncertain.…”
Section: Introductionmentioning
confidence: 99%